Investigation of aquifer distribution and groundwater quality in the Village of Rimbo Panjang, Kampar District - Riska Fitriani; Juandi Muhammad; Ari Sulistyo Rini (Science, Technology, and Communication Journal, 2020)
The study using the geoelectric method produces resistivity values with different color images. Data is displayed in the form of a collection of 1D and 2D pseudosection points which are then processed using Progress and Res2Dinv software. The 1D cross-section results in the appearance of the subsurface structure vertically or shows the depth and thickness of the subsurface layers. The results of Wenner and Schlumberger configuration data processing show that there are differences in resistivity and depth values on each path but have the same lithology. This is because the Schlumberger configuration can only display 1 point of depth vertically, so the data obtained cannot compare the resistivity horizontally. But the advantage of the Schlumberger configuration is that it is capable of displaying a large depth compared to the Wenner configuration so that it is difficult to read a thin layer of this configuration. The Wenner configuration result displays the depth and length of the layer along the track so that the thickness of the layer from the start of the track to the end of the track can be interpreted. The layer which has a small thickness can be identified using the Wenner configuration, but cannot reach any deeper depths.